UV degradation model for polymers and polymer matrix composites. (August 2018) - Lu, T.; Solis-Ramos, E.; Yi, Y.; Kumosa, M.
Abstract: We are proposing in this work a new model of ultraviolet (UV) damage for polymers and Polymer Matrix Composites (PMCs). Flat and sinusoidal polymer surfaces were numerically simulated for their UV damage as a function of UV intensity, surface topography, and exposure time. Experimentally determined UV degradation rates for a unidirectional glass/epoxy composite were used to predict numerically the local rates of material degradation on sinusoidal epoxy surfaces subjected to UV. This allowed us to show that UV damage on uneven polymer surfaces reduces their surface roughness making them planar and that the degradation rates are the largest at the tips of the local heights of the surfaces. This was subsequently verified experimentally by exposing neat epoxy specimens to UV in air at 80 °C for 1000 h and by precisely monitoring their surface topography as a function of time. It was found that the surface roughness of the epoxy was reduced by about 12.5% and that UV affected the local peaks on the surfaces of the specimens more than the valleys. Highlights: Sinusoidal polymer surfaces were numerically simulated for UV damage. UV intensity, surface topography, and exposure time were considered. UV damage on polymer surfaces reduces their surface roughness. This was subsequently verified experimentally.